PENGARUH PEMBIAYAAN JUAL BELI, PEMBIAYAAN BAGI HASIL, DAN NON PERFORMING FINANCE TERHADAP PROFITABILITAS (STUDI KASUS PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2012 - 2014) - Azhar, Ian; Nasim, Arim (Universitas Pendidikan Indonesia, 2016)
Abstract. This research aimed to find out the influence of Sale Financing, Profit Sharing Financing, and Non-Performing Finance toward Profitability. This research population is manufacturing firms that registered in The Indonesia Stock Exchange in the year of 2010-2012. By using purposive sampling method, 44 sample firms were selected. Method of analysis used in this research is pooled data regressions. The research population is an islamic commercial bank in Indonesia in the year of 2012-2014. By using saturated sampling method, 11 sample banks were selected. Method of analysis used in this research is linear regressions. The result of linear regressions showed that sale financing gives a positive influence toward profitability. While profit-sharing financing and nonperforming finance give negative influences toward profitability. And then, the result of hypothesis testing showed that sale financing, profit sharing financing, and non-performing finance an impact of 39.1 % toward profitability. While 60,9% is the influence of other variables than the sale financing, profit sharing financing, and non-performing finance.Keywords: sale financing; profit sharing financing; non-performing finance; return on asset; profitabilityÂ Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh Pembiayaan Penjualan, Pembiayaan Bagi Hasil, dan Non Performing Finance terhadap Profitabilitas. Populasi penelitian ini adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia pada tahun 2010-2012. Dengan menggunakan metode purposive sampling, 44 perusahaan sampel dipilih. Metode analisis yang digunakan dalam penelitian ini adalah penggabungan data regresi. Populasi penelitian adalah bank umum syariah di Indonesia pada tahun 2012-2014. Dengan menggunakan metode sampling jenuh, 11 bank contoh dipilih. Metode analisis yang digunakan dalam penelitian ini adalah regresi linier. Hasil regresi linier menunjukkan bahwa pembiayaan penjualan memberikan pengaruh positif terhadap profitabilitas. Sedangkan pembiayaan bagi hasil dan keuangan bermasalah memberikan pengaruh negatif terhadap profitabilitas. Dan kemudian, hasil pengujian hipotesis menunjukkan bahwa pembiayaan penjualan, pembiayaan bagi hasil, dan kinerja non performing berdampak pada 39,1% terhadap profitabilitas. Sedangkan 60,9% adalah pengaruh variabel lain dari pada pembiayaan penjualan, pembiayaan bagi hasil, dan keuangan non performing.Kata Kunci: pembiayaan penjualan; pembiayaan bersama; keuangan bermasalah; return on asset; profitabilitas